2016
DOI: 10.4103/0976-3147.185507
|View full text |Cite
|
Sign up to set email alerts
|

Role of ankle foot orthosis in improving locomotion and functional recovery in patients with stroke: A prospective rehabilitation study

Abstract: Objective:To study role of ankle foot orthosis (AFO) in improving locomotion and functional recovery after stroke.Setting:Neurological Rehabilitation Department of a university research tertiary hospital.Patients and Methods:AFO and activity based rehabilitation.Main Outcome Measures:Distance (meters) covered during the 6-minute walk test (6MWT) and speed (meter/second) during the 10-meter walk test. Functional abilities assessed using Functional Independence Measure (FIM®).Results:Twenty-six patients (21 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
(29 reference statements)
0
20
0
2
Order By: Relevance
“…During the operation of functional taping, a large pulling force is applied to the taping which may be similar to the AFO that promotes the improvement of walking and balance function [33]. Previous studies have demonstrated that the use of AFO is conducive to the normal posture of stroke patients in the normal movement pattern during training through the accumulation of feedback for positive reinforcement to establish the correct body pattern [34]. In this study, kinesio taping could produce an immediate effect on correcting the position of the ankle, increasing the walking efficiency, and improving the walking function, which may assist with the development of related rehabilitation training.…”
Section: Discussionmentioning
confidence: 99%
“…During the operation of functional taping, a large pulling force is applied to the taping which may be similar to the AFO that promotes the improvement of walking and balance function [33]. Previous studies have demonstrated that the use of AFO is conducive to the normal posture of stroke patients in the normal movement pattern during training through the accumulation of feedback for positive reinforcement to establish the correct body pattern [34]. In this study, kinesio taping could produce an immediate effect on correcting the position of the ankle, increasing the walking efficiency, and improving the walking function, which may assist with the development of related rehabilitation training.…”
Section: Discussionmentioning
confidence: 99%
“…AFO use is suggested to overcome such problem. Sankaranarayan et al [21] conducted a study of the gait of 26 stroke survivors with spasticity who applied AFOs. The study findings showed that using an AFO could positively influence the walking speed of hemiplegic stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Ukoliko bolesnik može sjediti, ruka se oslanja na stol u položaju antefleksije u ramenu od 90° i fleksije u laktu od 90° uz podlakticu u srednjem položaju između supinacije i pronacije s cilindričnim objektom u šaci 26 . Korištenje ortoze za gležanj i stopalo može umanjiti rizik od kontrakture stopala u plantarnoj fleksiji uz poboljšanje biomehanike hoda 27 . U kasnijem tijeku razvoj kontrakture zglobova povezan je sa stupnjem spasticiteta, bolom i smanjenom funkcionalnosti ekstremiteta.…”
Section: Prevencija Kontrakturaunclassified